PERAN PEMERINTAH KOTA SAMARINDA DALAM PEMENUHAN HAK PEREMPUAN DAN ANAK SEBAGAI IMPLEMENTASI PERATURAN DAERAH KOTA SAMARINDA NOMOR 2 TAHUN 2020 TENTANG PENGARUSTAMAAN GENDER DALAM PEMBANGUNAN DAERAH - Syifa Hajati; Alfitri Alfitri; Muhammad Idzhar (Fasya UIN Sultan Aji Muhammad Idris Samarinda, 2026)
The Government of Samarinda City has enacted Regional Regulation Number 2 of 2020 concerning Gender Mainstreaming (PUG) as part of its mission to achieve gender equality and justice. Based on this, the researcher is interested in examining the following issues: (1) What are the rights of women and children guaranteed in the Regional Regulation on Gender Mainstreaming?; (2) What is the role of the Samarinda City Government in ensuring and protecting the rights of women and children?; and (3) How is the legal review of the implementation of the Regional Regulation on Gender Mainstreaming? This research is a type of Normative-Empirical legal research (applied law research). The data were analyzed qualitatively using deductive reasoning, and based on Lawrence Meir Friedman’s legal system theory, which consists of legal structure, legal substance, and legal culture. The results of this research show that, first, the Regional Regulation on Gender Mainstreaming regulates the rights of women and children in general terms, through a clause stating that the roles, positions, and responsibilities of women are equal to those of men as development resources. Second, the role of the Samarinda City Government in ensuring and protecting the rights of women and children is carried out by making efforts to implement gender mainstreaming based on the Regional Regulation. Third, from the perspective of legal system theory, the implementation of the Regional Regulation on Gender Mainstreaming shows inconsistencies between the regulation and its implementing policies. In terms of substance, the regulation normatively outlines efforts to achieve equality in women's roles across various sectors.